The Lithuanian SSR students’ practical activity and knowledge of the field of environmental protection - Šalkauskas, A. (Psichologija, 1968)
Lithuanian SSR school students do plenty to preserve national wildlife. Many schools organize various extracurricular and after school actives for this purpose. An increasing number of students takes part in the national Natural Care competition and achieves better results. Materials analysis showed that the 7th grade students’ knowledge of nature conservation issues is shallow, fragmented, and not linked to their practical activities. Only 2.4% of students answered the question about what kind of institutions and organizations contribute to wildlife protection in our republic correctly and completely; 87.4% answered correctly, but incompletely, giving just one agency or organization. Only 6% of students answered the question about how birds are useful for farms correctly and completely; 94% answered correctly, but incompletely. Only a few students reported that birds catch mice, voles, and ground squirrels (11 questionnaires of 400) that they distribute seeds (4 questionnaires), and that the birds eat a significant amount of weeds (1 questionnaire). Students are only introduced to a little of the republic’s fauna and its protection. In response to the question about industrial fish, not a single student could name inland industrial fish like roach, bleak, vendace. Only 6% of students identified bream as an industrial fishing of the republic, 4% vimba vimba, and so on. The students are ignorant of the republic’s rules on reserves, sanctuaries, hunting, and fishing. Therefore, biology teachers aren’t using enough lesson time as a basis for instruction on the topic of environmentalism. The students’ practical activity is directed to theoretical knowledge; students are insufficiently introduced to local fauna.